Molecular Detection of Natural Babesia bovis Infection from Clinically Infected and Apparently Healthy Water Buffaloes (Bubalus bubalis) and Crossbred Cattle - Mahmmod, Yasser Saadeldien (Journal of Buffalo Science, 2012)
Babesia bovis (B. bovis) is a major causative agent of bovine babesiosis, with a considerable worldwide impact. The objective of this study was to evaluate the usefulness of PCR assay and microscopical examination (ME) for detection of B. bovis in naturally infected and apparently healthy water buffaloes and crossbred cattle under field circumstances from Sharkia province of Egypt. A total 34 animals (20 crossbred cattle and 14 buffaloes) were clinically and laboratory investigated during the period from March to August 2008. Fifteen animals showed symptoms of bovine babesiosis while 19 animals were apparently healthy. Two blood samples were collected from each animal; one was used for preparation of Giemsa-stained smears for ME while the other sample was used for DNA extraction and PCR testing. Out of 34 cattle and buffaloes, ME identified 13 animals (38.2%) as infected by B. bovis whereas PCR identified 29 (85.3%). B. bovis infected animals showed high fever, anaemia, jaundice, haemoglobinuria, and accelerated heart and respiratory rates. Out of 15 animals clinically infected, PCR identified 14 animals (93.3%) as infected while ME identified only, 8 animals (53.3%). Out of 19 animals apparently healthy, 5 animals (26.3%) were identified as infected by ME meanwhile 15 animals (78.9%) were identified by PCR. In conclusion, our findings demonstrated that water buffalos are likely to have a natural tolerance to B. bovis pathogen and/or more likely to be persistent carriers which were not picked up by microscopy. The severity of clinical symptoms of B. bovis infection on water buffaloes was less than the severity of clinical symptoms appeared on cattle. PCR assay is more sensitive technique than microscopical examination for detection of B. bovis in both clinically infected and apparently health cattle and water buffaloes which suggests its use as a routine technique for diagnosis of bovine babesiosis.